1997
DOI: 10.3354/meps153167
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in C, N and P budgets and tissue composition of the mussel Mytilus edulis

Abstract: Net C , N and P budgets of mussels were measured monthly in a field laboratory for a year. The calculated scope for growth was compared with the observed growth rates per month, for each element. Assuming ambient food, scope for growth was calculated and compared with changes in the tissue composition of mussels from a n estuarine field population. When total organic material was used as food, the calculated scope for growth overestimated the actual growth rates throughout the year. When phytoplankton was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 26 publications
3
37
1
Order By: Relevance
“…The mean N content of macroalgae was assumed to be 4.2% of DW (Yang et al 2006), and the C content of dry flesh of blue mussel was assumed to be 37% (Smaal & Vonck 1997). The dry matter contents of fresh seaweed and blue mussel from our own experiments were approximately 15% and 25%, respectively.…”
Section: Potential Of Macroalgae and Blue Mussel Productionmentioning
confidence: 90%
“…The mean N content of macroalgae was assumed to be 4.2% of DW (Yang et al 2006), and the C content of dry flesh of blue mussel was assumed to be 37% (Smaal & Vonck 1997). The dry matter contents of fresh seaweed and blue mussel from our own experiments were approximately 15% and 25%, respectively.…”
Section: Potential Of Macroalgae and Blue Mussel Productionmentioning
confidence: 90%
“…As Se is incorporated into cells as selenoamino acids (i.e. selenocysteine; Hatfield et al 1999) and selenoproteins (Vanda Papp et al 2007), strong variation in the relative elemental composition of soft tissues during spawning (Smaal & Vonck 1997) or as a result of nutrient stress (Okumura et al 2002) could indicate effects on the nitrogen pool that binds Se within the organism relative to body weight. But this physiological condition was not indicated by the consistent C:N ratios of Potamocorbula amurensis across the samples (spatial, seasonal or interannual) in the time series.…”
Section: Influence Of Clam Size and Nutrition On Se Concentrationsmentioning
confidence: 99%
“…Shifts in δ 15 N signatures of nutrients taken up into phytoplankton and propagated up food webs may also occur depending on nitrogen loading and nitrogen recycling (Canuel et al 1995, Cabana & Rasmussen 1996, Cloern et al 2002. Elemental concentrations of carbon and nitrogen (molar ratios) in invertebrates are a qualitative indicator of the nutritional quality of food consumed (Elser et al 2000) and have been shown to reflect short-term changes in nutrient status of the environment (Smaal & Vonck 1997). Subsamples of soft tissues of clams were analyzed for carbon and nitrogen content (i.e.…”
mentioning
confidence: 99%
“…The experimental time was adjusted so that the maximum reduction in particle concentration was 30% (Smaal & Vonck, 1997;Wong & Cheung, 2001). After cultivation, three replicates of 500 ml water samples and all produced fecal pellets were collected from the six sets of systems and filtered through pre-weighed ashless 47 mm GF/C filters and rinsed with double distilled deionized water to remove salt adsorbed on the surface of particles or filter paper.…”
Section: Determination Of Feeding Processes Of Epifaunal Organismsmentioning
confidence: 99%
“…Oxygen consumption was converted to C excretion based on a mean respiratory quotient (the ratio between carbon dioxide formed and oxygen used) of 0.85:1 μg O 2 ≡ 0.32 μg C. For C, excretion is zero, while for N and P, respiration is zero (Hawkins & Bayne, 1985;Smaal & Vonck, 1997). The assimilation of the nutrients by the organisms during each bimonthly test interval was estimated as:…”
Section: Nutrient Element Assimilationmentioning
confidence: 99%